"Inside out" growth method for high-quality nitrogen-doped graphene. (January 2021) - Fiori, Sara; Perilli, Daniele; Panighel, Mirco; Cepek, Cinzia; Ugolotti, Aldo; Sala, Alessandro; Liu, Hongsheng; Comelli, Giovanni; Di Valentin, Cristiana; Africh, Cristina
Abstract: High-quality nitrogen-doped graphene on nickel is prepared by exploiting both the catalytic properties of nickel and the solubility of nitrogen atoms into its bulk. Following the standard chemical vapor deposition procedure, a previously nitrogen-doped nickel substrate is exposed to carbon-containing precursors so that nitrogen atoms, segregating to the surface, remain trapped in the growing graphene network. Morphological and chemical characterization by scanning tunneling microscopy and X-ray photoelectron spectroscopy demonstrates that the process yields a flat, wide, continuous nitrogen-doped graphene layer. Experimental results are combined with a thorough density functional theory investigation of possible structural models, to obtain a clear description at the atomic scale of the various configurations of the nitrogen atoms observed in the graphene mesh. This growth method is potentially scalable and suitable for the production of high-performance nano-devices with well-defined nitrogen centers, to be exploited as metal-free carbon-based catalysts in several applicative fields such as electrochemistry, energy storage, gas storage/sensing or wastewater treatment. Graphical abstract: Image 1 Highlights: An alternative method for nitrogen doped graphene growth in vacuum is developed. The introduction of nitrogen dopants from the Ni bulk preserves graphene quality. Nitrogen doping centers fully are characterized by microscopy and theory. Graphitic and pyridinc nitrogen defects are identified in the graphene layer. Stable configurations of C vacancies in graphene surrounded by nitrogen atoms found.